Case Study : Naelofar Hijab / Nur Masyitah Syarah Mohd Zamri - Mohd Zamri, Nur Masyitah Syarah (2021)
An entrepreneur is someone who takes on an entrepreneurial venture to create something new that solves a problem; small business ownership and franchising are also entrepreneurial options. The venture could be for profit or not for profit, depending on the problem it intends to solve. Entrepreneurs can remain in a full-time job while pursuing their ideas on the side, in order to mitigate risk. On the opposite end of the spectrum, entrepreneurs can take on lifestyle ventures and become serial entrepreneurs. There are many factors driving the growth of entrepreneurship, including employment instability, motivation to create something new, financial factors and free time associated with retirement, and the greater acceptance of entrepreneurship as a career choice.